TparvaDB: A database to support Theileria parva vaccine development - Visendi, P.; Ng'ang'a, W.; Bulimo, Wallace; Bishop, Richard P.; Ochanda, J.; Villiers, Etienne P. de (Oxford University Press, 2011)
We describe the development of TparvaDB, a comprehensive resource to facilitate research towards development of an East Coast fever vaccine, by providing an integrated user-friendly database of all genome and related data currently available for Theileria parva. TparvaDB is based on the Generic Model Organism Database (GMOD) platform. It contains a complete reference genome sequence, Expressed Sequence Tags (ESTs), Massively Parallel Signature Sequencing (MPSS) expression tag data and related information from both public and private repositories. The Artemis annotation workbench provides online annotation functionality. TparvaDB represents a resource that will underpin and promote ongoing East Coast fever vaccine development and biological research.